PENILAIAN KONDISI DAN PREDIKSI UMUR SISA BERDASARKAN BRIDGE MANAGEMENT SYSTEM 1993 (STUDI KASUS JEMBATAN ATINGGOLA, PROVINSI GORONTALO) - Khairinnisa Rustawa, Nita Widia; -, Sumargo (Universitas Islam 45, 2021)
Bridge inspection is the process of collecting physical data to ensure that the bridge is safe and thus securing the investment value of the bridge. Inspection results are used for planning the program of maintenance, rehabilitation, strengthening, and replacement of bridges. In this study, the assessment of the Atinggola bridge condition, located in Gorontalo Province, Indonesia, uses the reference standard from the Bridge Management System 1993, including the bridge top structure, the bridge bottom structure, complementary structures, and the river basin around the bridge. Previous bridge condition data which are based on the inspection result in 2017 are used as a comparison for the future. Condition values are used to predict the remaining life of a bridge using an equation developed by Bina Marga. Overall result shows the value of the bridge condition is 2 with the predicted remaining life of the bridge is 18.88 years. These results indicate that the bridge suffered minor damage and need routine maintenance. Therefore, the bridge is able to perform optimally until the end of the planned life.